Gut microbiota analyses of cutaneous T-cell lymphoma patients undergoing narrowband ultraviolet B therapy reveal alterations associated with disease treatment - Nguyen, William Q.; Chrisman, Lauren P.; Enriquez, Gail L.; Hooper, Madeline J.; Griffin, Teresa L.; Ahmad, Merjaan; Rahman, Sophia; Green, Stefan J.; Seed, Patrick C.; Guitart, Joan; Burns, Michael B.; Zhou, Xiaolong A. (Frontiers in Immunology, 2024)
Recent studies have shown a close relationship between cutaneous T-cell lymphoma (CTCL) and its microbiome. CTCL disease progression is associated with gut dysbiosis and alterations in bacterial taxa parallel those observed in immunologically similar atopic dermatitis. Moreover, the microbial profile of lesional skin may predict response to narrowband ultraviolet B (nbUVB), a common skin-directed therapy. However, the relationship between the gut microbiome, an immunologically vital niche, and nbUVB remains unexplored in CTCL. Herein, we performed 16S rRNA sequencing and PICRUSt2 predictive metagenomics on DNA extracted from stool swabs of 13 CTCL patients treated with nbUVB, 8 non-treated patients, and 13 healthy controls. Disease response was assessed with modified Severity Weighted Assessment Tool (mSWAT); of nbUVB-treated patients, 6 improved (decreased mSWAT), 2 remained stable, and 5 worsened (increased mSWAT). Protective commensal bacteria including Lactobacillaceae and Erysipelatoclostridiaceae were significantly less abundant in CTCL patients compared to controls. With treatment, the CTCL gut microbiome exhibited decreased phylogenetic diversity and lower relative abundance of proinflammatory Sutterellaceae. Sutterellaceae was also significantly more abundant in patients who worsened, and Eggerthellaceae and Erysipelotrichaceae trended higher in patients who improved. Finally, PICRUSt2 functional predictions based on shifts in abundance of bacterial sequences repeatedly identified alterations in inositol degradation, which plays a key role in host immunomodulation, including inositol phospholipid signaling relevant to T-cell survival and proliferation. Our results bolster the paradigm of gut dysbiosis in CTCL and its functional implications in disease pathogenesis, and further delineate bacterial taxa associated with nbUVB response and with nbUVB treatment itself.